The Engagement of Critical and Creative Thinking Activities in the Teaching and Learning Process - Tiong, Gan Hock; Bakar, Abu Yazid Abu (ASEAN Journal of Educational Research and Technology, 2022)
The new challenges of the education process at all levels currently vary in different dimensions and perspectives.  One of them is to inculcate the critical and creative thinking ability among the students, specifically for students in the Y, Z, and Alpha generations.  Many researchers and scholars indicate that since the beginning of the 21st century and the possession of unique characteristics among the millennial generations, the future education system must be also revolutionized so that it will always be relevant and effective in holistically developing the future generation of a particular nation.  One of the ways to do this is by engaging critical and creative thinking activities in the daily teaching and learning process at schools and higher learning institutions.  This concept paper discusses the need for such engagement from a Malaysian perspective.